Effect of Adjuvant Chemotherapy on Left Ventricular Remodeling in Women with Newly Diagnosed Primary Breast Cancer: A Pilot Prospective Longitudinal Cardiac Magnetic Resonance Imaging Study. Issue 6 (November 2017) - Avelar, Erick; Truong, Quynh A.; Inyangetor, David; Marfatia, Ravi; Yang, Clifford; Kaloudis, Electra; Tannenbaum, Susan; Rosito, Guido; Litwin, Sheldon
Abstract : Purpose: The aim of this study was to assess the left ventricular (LV) remodeling response to chemotherapy in low–cardiac-risk women with newly diagnosed nonmetastatic breast cancer. Cardiotoxic effects of chemotherapy are an increasing concern. To effectively interpret cardiac imaging studies performed for screening purposes in patients undergoing cancer therapy it is necessary to understand the normal changes in structure and function that may occur. Methods: Twenty women without preexisting cardiovascular disease, of a mean age of 50 years, newly diagnosed with nonmetastatic breast cancer and treated with anthracycline or trastuzumab, were prospectively enrolled and evaluated at four time points (at baseline, during chemotherapy, 2 weeks after chemotherapy, and 6 months after chemotherapy) using cardiac magnetic resonance imaging, blood samples, and a clinical questionnaire. Results: Over a 6-month period, the left ventricular ejection fraction (%) decreased (64.15±5.30 to 60.41±5.77, P <0.002) and the LV end-diastolic (mm) and end-systolic (mm) volumes increased (124.73±20.25 to 132.21±19.33, P <0.04 and 45.16±11.88 to 52.57±11.65, P <0.00, respectively). The LV mass (g) did not change (73.06±11.51 to 69.21±15.3, P =0.08), but the LV mass to LVEDV ratio (g/mm) decreased (0.594±0.098 to 0.530±0.124, P <0.04). Conclusions: In low–cardiac-risk women with nonmetastatic breast cancer, the increased LV volume and a mildly decreased left ventricular ejection fraction during and after chemotherapy do not seem to be associated with laboratory or clinical evidence of increased risk for heart failure.